Water Quality of Urban Streams: The Allium cepa Seeds/Seedlings Test as a Tool for Surface Water Monitoring - Camila Gonçalves Athanásio; Daniel Prá; Alexandre Rieger (The Scientific World Journal)
The present study investigates the genotoxic, mutagenic, and cytotoxic potential of surface waters in urban streams using Allium cepa and analyzes the applicability of this assay for environmental monitoring. Water samples were collected from three streams located in the urban area of a municipality in the south of Brazil. For each stream, two samples were collected, one upstream and one downstream of the pollution discharge site. Physicochemical evaluation indicated that all samples had various degrees of environmental impact, but substantial impact was seen for the downstream samples of the Preto and Pedras streams. All samples increased the frequency of chromosome aberrations (P<0.05). The sample from Pedras downstream site also caused a decrease in mitotic index (P<0.08) and increase in micronuclei (P<0.08) frequency, indicating potential cytotoxicity and mutagenicity. The Pedras stream receives mixed industrial and urban wastewater, while the Lajeado and Preto streams receive wastewater predominantly domestic in nature, which may partially explain the difference in toxicity among the samples. Moreover, the Allium cepa seeds/seedlings were shown to be extremely sensitive in detecting the genotoxicity of environmental water samples and can be applied as the first tool for environmental health hazard identification and prediction.